Introduce decent standard of living guide for all - Mat Ghani, Gairuzazmi (2020)
Department of Statistics Malaysia (DOSM) announced a revision of the national Poverty Line Income (PLI) from RM980 to RM2,208. However, the PLI does not take into account the cost of living beyond a very basic budget. It does not take into consideration expenditures like childcare, leisure, and social activities that not only draw from a household's income but are also determining factors in a person's ability to work and endure the potential hardships associated with balancing employment and other aspects of everyday life.